Enhanced Anti-E. coli ST131 Metabolites Production by a Novel Streptomyces sp. CMB51 Strain Isolated from a Coal Mininig Soil Using Statistical Optimization. Issue 1 (2nd January 2022) - Djinni, Ibtissem; Djoudi, Warda; Harfi, Nadia; Stambouli, Imene; Khamtache, Sara; Makhlouf, Djaouida; Yanat, Betitera; Souagui, Samiha; Kecha, Mouloud
Abstract: Actinobacteria strains isolated from coil mining soil of Bechar region, Algeria, were evaluated for their antimicrobial potential against pathogenic germs particularly against uropathogenic multiresistant Escherichia coli ST131. Of the 119 isolates, 82 exhibited potent antimicrobial properties. The strain that showed maximum inhibition against E. coli ST131 was further screened toward nine bacterial pathogens and identified based on morphological, physiological and 16S rRNA gene sequencing. The isolate was related to the genus Streptomyces with 99.46% sequence similarity to Streptomyces klenkii strain S2704 T and assigned as Streptomyces sp. CMB51. To achieve maximum metabolites production, significant process parameters were optimized through response surface methodology employing Plackett–Burman and Central Composite designs. In PBD experiments, starch and casein concentrations, incubation time and initial pH value emerged as the most significant affecting the output of anti- E. coli ST131 activity. The composition of the final optimized medium was soluble starch concentration of 5.31 g/L, casein concentration of 0.45 g/L, 3 days incubation time and 8.41 initial pH value. The optimization resulted an antibacterial activity of 13 mm which was in close accordance with the predicted value of 13.60 mm recording 18.18% increase. The chosen method was efficient for further investigations of the production of anti- E. coli ST131 metabolites.